THE READINESS OF ENGLISH COMMUNICATION SKILLS OF MATARAM TOURISM VOCATIONAL COLLEGE STUDENTS FOR ASEAN ECONOMIC COMMUNITY - Putra, Ida Nyoman Tri Darma (Journal of English Language Teaching, 2018)
The purpose of this study was to find out the readiness of English communication skills of tourism students at Mataram Tourism Vocational College to enter the ASEAN Economic Community era. The scope of this study includes students from three tourism study programs, namely diploma 3 programs in hotel and hospitality, diploma 3 tours and travel and bachelor program in tourism. A total of 110 respondents were used in this study. Four English communication skills including listening, speaking, reading, and writing are measured using questionnaires as instruments for collecting data. Statistical analysis includes percentages, averages, and standard deviations. The research findings revealed that Tourism students at STP Mataram need to develop and improve their skills in English communication, especially listening and speaking which is a skill needed to communicate with foreigners, especially in NTB. From the four skills of language, STP Mataram student Language skills are not ready to communicate using English, 30% respondents answered that they have not been able or disagree from the questionnaire.